Domestic abuse : contemporary perspectives and innovative practices - Brooks-Hay, Oona; Burman, Michèle; McFeely, Clare (Edinburgh : Dunedin Academic Press, 2018)
Domestic abuse is a global health and social problem. This edited volume considers Scottish responses in a wide comparative context.
Description based on print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Family violence; POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; Electronic books